Integrating content-based language learning and intercultural learning online: An international eGrops collaboration - Walker, Ute Gerda; vom Brocke, Christina (My University, 2009)
Learning language through content in the tertiary context presents a challenge in that language teachers, particularly in EAP/ESP contexts, are not necessarily experts in their students’ speciality subject areas, while subject experts might lack language teaching methodology. Furthermore, intercultural awareness, a key qualification in today’s global work environment, tends to take a back seat in a content-based approach. This paper reports on a didactic concept which integrates subject-based language learning with intercultural experience through online collaboration in an international eGroups set-up. The creation of a collaborative learning space aimed to bring together learners from different cultural contexts (New Zealand and Germany) and with different target languages (German and English) towards shared learning outcomes. Data from student interactions will help illustrate to what extent the eGroups model promoted interactive, communicative and intercultural competence through content-related bilingual collaboration.
Keywords: Online collaboration; English language; German language; CALL; EAP/ESP; Intercultural learning; e-groups; Fields of Research::420000 Language and Culture::420100 Language Studies